RELATIONSHIP OF CHARACTERISTICS (AGE, SEX, LEVEL OF EDUCATION) WITH HYPERTENSION IN TRAINING OF HEALTHY FAMILY TRAINERS - Supriyono Supriyono; Agus Andriyanto (Universitas Muhammadiyah Kalimantan Timur, 2020)
Abstract:Background. Based on the results of the Basic Health Research (Riskesdas) in 2013, the prevalence of hypertension is still high at 25.8%, so hypertension is still one of the public health problems in Indonesia. Objectives. This study aims to determine the relationship of characteristics (age, gender, and level of education) with hypertension in participants of the Training of Healthy Family Trainers. Methods. This type of research is cross-sectional with a sample of 30 people. Data collection by interview and blood pressure examination. Interviews were conducted to find out data about respondents' characteristics which included age, gender and level of education. Whereas for blood pressure measurements are carried out with sphygmomanometer. Data analysis using statistical test Spearman Rank Correlation Test. Results. Based on the results of blood pressure measurements obtained the following results, blood pressure in the normal category = 23.30%, prehypertension = 53.3%, hypertension first degree = 16.7%, second degree hypertension = 3.3% and severe hypertension = 6.7%. From the statistical test, the results of p=age = 0.961 p sex = 0.172 p = education level = 0.679 (p> 0.05). Discussion. Age, gender and education are not the sole factors causing hypertension. Therefore, to reduce hypertension, it is necessary to apply clean and healthy living behaviours Conclusion. There is no relationship between age, sex and level of education with hypertension. Recommendation. Providing a health examination room in the form of a health clinic, which is equipped with human resources (doctors, nurses, midwives, and nutritionists) Keywords: Hypertension, Age, Gender, Education Level, Rank Spearman Correlation